GE_GERICHTE A/2371/2020 vom 29. März 2021 - GE Cour de justice (2021)
VALEUR FISCALE;IMMEUBLE;REVENU DE LA FORTUNE IMMOBILIÈRE(DROIT FISCAL);VALEUR LOCATIVE | LIPP.50.lete; LIFD.21.al1.letb; LIPP.24.al1.letb